Poly-symptomatology of chronic multi-canalicular benign paroxysmal positional vertigo: a deductive, inductive, and abductive narrative review - Tjell, Carsten; Iglebekk, Wenche; Borenstein, Peter (Frontiers in Neurology, 2025)
This narrative review aims to present an overview of the symptomatology of chronic multi-canalicular benign paroxysmal positional vertigo (mc-BPPV) from deductive (what is believed to be known), inductive (what is likely), and abductive (hypothetical) perspectives. The purpose is to recognize these symptoms as expressions of an eventual mc-BPPV when they occur in patients with vestibular migraine, whiplash associated disorders (WAD) and other chronic pain disorders. These symptoms are often considered to be biopsychosocial conditions due to a lack of objective findings, that is, the absence of the findings one is looking for—not the absence of findings generally. The symptomatology of mc-BPPV follows a basic neurophysiologic principle: a disorder in one part of the vestibular system often affects the functions of other parts of the vestibular system. In patients with chronic mc-BPPV, abnormal signals are transmitted as afferents to the vestibular nuclei complex; from there, consistently abnormal efferent reflexes are transmitted. These symptoms can include dizziness, visual disturbances, headache, neck pain, temporomandibular joint region pain, other musculoskeletal pain, involuntary movements, tinnitus, temperature disturbance, and cognitive dysfunction. Therefore, it is necessary to consider the possibility of mc-BPPV in patients with vestibular migraine, WAD and other chronic pain disorders.